BASIC SCENARIOS OF INVOLVEMENT FORCES AND MEANS OF CIVIL-MILITARY COOPERATION IN A COMBAT FORMATIONS IN THE COURSE OF PERFORMING APPOINTED TASKS DURING THE ARMED CONFLICTS SETTLEMENT - Mynko, Oleksandr (Honor and Law, 2022)
The main factor that will influence the creation of a system of civil-military cooperation at the tactical and operational levels has been identified. The results of the analysis of the main factor that will directly affect the commanderʼs intent to create a system of civil-military cooperation during special operations and combat actions are considered. The analysis of the guiding documents showed that the procedure for involving civil-military cooperation units of the National Guard of Ukraine and the tactics of their actions during the performance of combat missions as assigned during the settlement of armed conflicts are not defined. In the normal security situation conditions (normal operational situation, in the absence of collision with the enemy and in normal conditions, including criminogenic situation) civil-military cooperation units will be able to conduct their activities almost without restrictions, using a set of technologies to influence the civilian environment. Civil-military cooperation activities in situations of medium complexity (I Option), and in difficult situations (II Option) will be organized in the other way. Both options can be considered as basic scenarios for the involvement of civil-military cooperation forces during during special operations and combat actions. The variants of the procedure for involving the forces and means of civil-military cooperation of the National Guard of Ukraine in combat formations in the course of special operations and combat actions developed and improved during the research are considered. Typical schemes and descriptions of the order of actions of forces and means of civil-military cooperation of the National Guard of Ukraine in combat formations during special operations and combat actions during the armed conflicts settlement are proposed for consideration.